1992
DOI: 10.1152/ajpcell.1992.263.5.c917
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte K-Cl cotransport: properties and regulation

Abstract: Erythrocytes possess a Cl-dependent, Na-independent K transport system cotransporting K and Cl in a 1:1 stoichiometry that is membrane potential independent. This K-Cl cotransporter is stimulated by cell swelling, acidification, Mg depletion, and thiol modification. Cell shrinkage, elevation of cellular divalent ions, thiol alkylation, phosphatase inhibitors, and derivatives of certain loop diuretics and stilbenes are inhibitory. Thus regulation of K-Cl cotransport at the membrane and cytoplasmic levels is hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
194
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(202 citation statements)
references
References 99 publications
7
194
0
1
Order By: Relevance
“…Characterization of the K + influx via KCC and KNHE in the CHC patient's erythrocytes showed that the unusually high cation permeability in these cells at low temperature is, at least in part, a cumulative effect of an abnormal activation of two independent ion transport systems: KCC and KNHE. As follows from the Table 1, and in agreement with former reports, 22,30 both ion transporters are almost silent in RBC from healthy donors (and the patient's family members), particularly during cold storage. Several lines of evidence point towards an abnormally high activity of the cation-proton exchanger in RBC of the CHC patient at 37°C and even more so at 0°C.…”
Section: Discussionsupporting
confidence: 91%
“…Characterization of the K + influx via KCC and KNHE in the CHC patient's erythrocytes showed that the unusually high cation permeability in these cells at low temperature is, at least in part, a cumulative effect of an abnormal activation of two independent ion transport systems: KCC and KNHE. As follows from the Table 1, and in agreement with former reports, 22,30 both ion transporters are almost silent in RBC from healthy donors (and the patient's family members), particularly during cold storage. Several lines of evidence point towards an abnormally high activity of the cation-proton exchanger in RBC of the CHC patient at 37°C and even more so at 0°C.…”
Section: Discussionsupporting
confidence: 91%
“…LK sheep red cells are the more unusual in having a high passive K¤ 'leak' coupled with a small active K¤ uptake through the Na¤,K¤-ATPase (Tosteson & Hoffman, 1960); the reverse pertains for HK red cells. The large K¤ 'leak' in LK red cells is, in fact, a very specific anion-dependent transporter, exquisitely sensitive to volume, pH and urea (Dunham & Ellory, 1981;Lauf et al 1992 ;Dunham, 1995). It is almost certainly via the KCl cotransporter, recently cloned from human, rat and rabbit tissues (Gillen, Brill, Payne & Forbush, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent change in free [Mg¥]é may interact with the complex PPÏPK cascade regulating cotransport activity at several points (Lauf, Erdmann & Adragna, 1994;Flatman et al 1996). Certainly Mg¥ depletion or loading of red cells modulates cotransport activity (Delpire & Lauf, 1991;Lauf et al 1992) and, furthermore, changes in POµ are unable to alter cotransport activity in the absence of functioning PPÏPK enzymes (trout - Cossins, Weaver, Lykkeboe & Nielsen, 1994;horseHoness et al 1996). Pharmacologically, however, the sensitivity of the cotransporter to magnesium is low (Delpire & Lauf, 1991;Lauf et al 1992), and there is no definitive evidence that the magnitude of Oµ-dependent (physiological) flucations in free [Mg¥]é per se is sufficient to modulate cotransport activity.…”
Section: Intracellular Magnesium and Oµ Dependency Of K¤ Influxesmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, and given that K ϩ -Cl Ϫ cotransport is enhanced under conditions that lead to cell swelling, the KCCs are believed to play a key role in regulatory volume decrease responses (15)(16)(17). However, K ϩ -Cl Ϫ cotransport is not completely abolished under isotonic conditions (18 -20) 4 and is sensitive to changes in intracellular ionic strength (21)(22)(23), suggesting that the KCCs are also of central importance in intracellular Cl Ϫ (Cl i Ϫ ) regulation (22,23) and can thus affect a variety of physiological processes (24 -26).…”
mentioning
confidence: 99%